Aspects of Greek-Russian Relations in the Early Modern and Modern Periods (17th-20th Centuries) - Chrissidis, Nikolaos (Annuaire de l'École pratique des hautes études (EPHE), Section des sciences religieuses. Résumé des conférences et travaux, 2023)
This series of four presentations sought to examine case studies of Greek-Russian relations in the early modern and, mostly, modern period. In the choice of topics, I was guided by two considerations: first, I sought to highlight topics that, to my mind, have not yet attracted the attention they deserve in historiography. For example, although alms collections in the Russian Empire in the early modern period have been discussed repeatedly, this has not been the case until quite recently for t...
Keywords: Christianisme orthodoxe; Histoire des chrétiens d’Orient (XVIe-XXIe siècle); dept.his